1998
DOI: 10.1002/(sici)1097-461x(1998)69:3<387::aid-qua16>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

DFT investigations of the structure and bonding between transition metals and olefins

Abstract: ABSTRACT:The structure of ethylene, allyl, and butadiene -complexes with Ni 0 2q Ž . and Ni were optimized with density functional theory DFT . The different kinds of coordinative interaction between the olefins and the metal had been discussed for the frontier orbitals of the given symmetry. Both components of the donation and back-Ž . donation bond were characterized by charge density analysis CDA and natural bond Ž . orbital NBO populations. In case of the butadiene ligand the s-cis and s-trans conformer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…Ni 2þ (C 2 H 4 ) is predicted to be a C s structure (Alexander & Dines, 2004). For Ni 2þ -butadiene complexes, the h 4 -structure, in which the metal interacts with the four carbon atoms was the only local minimum found, for both the cis and the trans isomers, the former being 22 kJ/mol more stable (Bögel, Tobisch, & Nowak, 1998) than the latter.…”
Section: Ni 2þ -Complexesmentioning
confidence: 97%
See 1 more Smart Citation
“…Ni 2þ (C 2 H 4 ) is predicted to be a C s structure (Alexander & Dines, 2004). For Ni 2þ -butadiene complexes, the h 4 -structure, in which the metal interacts with the four carbon atoms was the only local minimum found, for both the cis and the trans isomers, the former being 22 kJ/mol more stable (Bögel, Tobisch, & Nowak, 1998) than the latter.…”
Section: Ni 2þ -Complexesmentioning
confidence: 97%
“…Theoretical studies on Ni 2þ complexes with ethene (Alexander & Dines, 2004) and butadiene (Bögel, Tobisch, & Nowak, 1998) concluded that the high positive charge on the metal reduces significantly backdonation interactions from the metal to the neutral base, and this diminishes also the donation from the carbon atoms since its positive charge is not compensated through the backdonation. Consistently, the geometry distortions in both ethane and butadiene are smaller in Ni 2þ than in Ni 0 complexes.…”
Section: Ni 2þ -Complexesmentioning
confidence: 99%
“…Hence, it is observed that though there is a change in the relative stabilities, the ground-state geometry of the Ni(C 4 H 6 ), obtained in our calculations, has remained unaffected by the choice of basis set. Therefore, on the basis of this observation, we conclude that the disagreement between our calculated results and the previous calculations 6 can be attributed to the choice of the energy functionals and to a lesser degree on the choice of different basis sets. The structural parameters of the η 4 -trans and η 2 -trans complexes obtained from our calculations are in good agreement with the previous calculations.…”
Section: Resultsmentioning
confidence: 60%
“…Theoretical calculations on Ni-butadiene complex are limited. A semiempirical calculation on Ni(C 4 H 6 ) complex, 5 and a DFTbased calculation 6 on Ni interaction with ethylene, and butadienes have been reported previously. In the DFT-based investigation, 6 only Ni(C 4 H 6 ) and Ni 2+ (C 4 H 6 ) complexes were taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation